1994
DOI: 10.1084/jem.180.5.1973
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of human T cell lymphotropic virus type 1 (HTLV-1) sequences in peripheral blood mononuclear cells from patients with mycosis fungoides.

Abstract: SummaryMycosisfungoides (MF) is a rare form of cutaneous T cell lymphoma suspected of having a viral etiology. As in adult T cell leukemia, the virus involved may be human T lymphotropic virus type 1 (HTLV-1). We cultured the peripheral blood mononuclear cells (PBMC) of 29 patients with MF HTLV-1 seronegative by enzyme-linked immunosorbent assay and Western blot. The presence of reverse transcriptase (RT) and p24 antigen was investigated in the concentrate supematant of the culture. The DNA of all studied pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
15
1
1
Order By: Relevance
“…Some cases may represent misdiagnosis of MF in patients with smouldering ATLL. However, most cases of ATLL are seropositive and most reported cases of HTLV-I in CTCL are in seronegative individuals (D'Incan et al, 1990;Dave et al, 1995;Fouchard et al, 1995;Ghosh et al, 1994;Hall et al, 1991;Lisby et al, 1992;Manca et al, 1994;Pancake et al, 1995;Whittaker & Luzatto, 1993;ZuckerFranklin et al, 1991ZuckerFranklin et al, , 1992. Rare cases of HTLV-I antibody negative ATL have been described (Korber et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cases may represent misdiagnosis of MF in patients with smouldering ATLL. However, most cases of ATLL are seropositive and most reported cases of HTLV-I in CTCL are in seronegative individuals (D'Incan et al, 1990;Dave et al, 1995;Fouchard et al, 1995;Ghosh et al, 1994;Hall et al, 1991;Lisby et al, 1992;Manca et al, 1994;Pancake et al, 1995;Whittaker & Luzatto, 1993;ZuckerFranklin et al, 1991ZuckerFranklin et al, , 1992. Rare cases of HTLV-I antibody negative ATL have been described (Korber et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al (1994) documented the presence of HTLV-I tax and/or rex proviral sequences in 72% of uncultured peripheral blood mononuclear cells (PBMCs) and 80% of T-cell lines derived from patients with SS. The same year, Manca et al (1994) found PCR amplification of HTLV-I pol and pX regions in cultured cells from 10/29 Italian patients with MF. In contrast, at least six reports fail to confirm these observations (Table I) (Abrams et al, 1991;Bazarbachi et al, 1993;Capesius et al, 1991;Lisby et al, 1992;Moudgil et al, 1994;Pombo de Oliviera et al, 1995;Vallejo et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although viral transformation with human T-cell lymphotropic virus type 1 has been found in some cases of CTCL, 3 it does not seem to be the agent causing MF. 4 Thus, the primary etiology of MF remains to be found.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Several groups have thus demonstrated HTLV-I proviral fragments -mostly tax -in DNA extracted from PBMC and/or cutaneous lesions by PCR, in HTLV-I-seronegative SS and MF patients. 17,18,[56][57][58] In Africa, HTLV-I has recently been isolated from a transformed T cell line spontaneously derived from PBMC of a seronegative Egyptian patient with MF. 35 In contrast, other groups failed to detect such HTLV-I sequences in similar patients.…”
Section: Discussionmentioning
confidence: 99%